winter_base - Lafontaine, Alexandre; Drapeau, Pierre; Fortin, Daniel; St-Laurent, Martin-Hugues (Dryad Digital Repository, 2017)
Data used in the resource selection function analysis linking habitat selection to range fidelity and adult female survival during winter.